Factors related to office layout that effects employee’s productivity at Petronas Penapisan (Melaka) Sdn. Bhd. / Nur Nadirah Yusop and Nurulain Yunus - Yusop, Nur Nadirah; Yunus, Nurulain (Faculty of Business and Management, 2013)
This paper present the analysis on the relationship between the office layout elements and employees productivity. The research focused on four elements that necessarily related to designing a conducive office layout which is Spatial Arrangement, Temperature, Noise and Lighting and investigates it relationship towards determining employees productivity. Three objectives are presented which is first, to highlight the needs of better workplace for improving employees productivity, second to determine the effect of office layout on employee productivity and the third objectives are to analyze features which employee value in their office layout. All three objectives aimed for a improving the workplace for betterment thus increase employees work quality. For this purpose, 109 reliable respondent from PETRONAS Penapisan Melaka Sdn Bhd were studied and findings results shows that the four elements of office layout has a substantial influence on employees productivity. Findings on this research shows a positive relationship between the four independent variables with the dependent variable which is productivity whereby spatial arrangement at (r = 0.523, P < 0.01), temperature at (r = 0.547, P < 0.01), noise at (r = 0.523, P < 0.01) and lighting at (r = 0.523, P < 0.01).